794 nm excited core–shell upconversion nanoparticles for optical temperature sensing. Issue 14 (28th January 2016) - Jiang, Guicheng; Zhou, Shaoshuai; Wei, Xiantao; Chen, Yonghu; Duan, Changkui; Yin, Min; Yang, Bin; Cao, Wenwu
Abstract : Nd 3+ sensitized core–shell upconversion nanoparticles (UNCPs) are promising candidates for application in optical temperature sensors at a biocompatible excitation wavelength (794 nm). Abstract : Hexagonal core–shell NaYF4 upconversion nanoparticles (UNCPs) based on Nd 3+ sensitization for optical temperature sensing were successfully synthesized by a solvothermal method using oleic acid and octadecene as coordinating solvents. Compared to the conventional Yb 3+ sensitized UNCPs, the usage of Nd 3+ as the sensitizers can shift the excitation wavelength from 975 nm to 794 nm where the optical absorption of water decreased dramatically, and thus make UNCPs more suitable for biological application. The upconversion (UC) luminescence intensity of the 794 nm-excitation UNCPs is comparable to that of the conventional 975 nm excitation, showing that Nd 3+ sensitized UNCPs are efficient. The efficiently successive Nd 3+ → Yb 3+ → Er 3+ energy transfer processes in this UNCP were demonstrated by excitation spectra and time-resolved spectra. The temperature dependence of the fluorescence intensity ratios (FIR) for the two green emissions (525 nm and 545 nm) from the thermally coupled levels of Er 3+ was studied in the temperature range from 25 to 60 °C under 808 nm excitation, and the temperature mapping of a device was acquired according to this technique. These indicate that Nd 3+ sensitized core–shell UNCPs are promising candidates for application in optical temperature sensors.